Beyond Branches: How Fintech and Sustainable Innovation are Reshaping The Banking Landscape in Indonesia - Sendjaja, Theodorus; Rachbini, Didik J.; Astini, Rina; Asih, Daru (Applied Business and Administration Journal, 2024)
This research underscores the critical role of innovation and sustainability in the financial services industry as businesses strive to remain competitive. It sheds light on the widespread closure of bank branches on a global scale, emphasizing the delicate balance required between embracing digital advancements and maintaining a physical presence to ensure competitiveness and meet evolving consumer needs. The Systematic Literature Review focuses on two primary areas—sustainable digital technology innovation in Fintech and banks' digital transformation—and compiles theoretical references pertinent to sustainable innovation in financial institutions. The evolution of technology influences digital business models, and the aim is to implement digital service-oriented policies to ensure long-term business sustainability. Fintech has the potential to change the business and economic landscape fundamentally. The advantages of fintech are as follows: innovative, faster, flexible, interactive, diverse applications, disruptive thinking, and design thinking. The suggested digital transformation approach for the Bank's ongoing innovation: making digital a key value in business, customer-centricity, openness principles, and regulatory compliance.Keywords: Bank, Digital Transformation, Fintech, Innovation, Sustainability